Patient-Centered Medical Home With Colocation: Observations and Insights From an Academic Family Medicine Clinic - George G. A. Pujalte; Sally Ann Pantin; Thomas A. Waller; Livia Y. Maruoka Nishi; Floyd B. Willis; Tarang P. Jethwa; Richard J. Presutti (SAGE Publishing, 2020)
There is a movement in the United States to transform family medicine practices from single physician-based patient care to team-based care. These teams are usually composed of multiple disciplines, including social workers, pharmacists, registered nurses, physician assistants, nurse practitioners, and physicians. The teams support patients and their families, provide holistic care to patients of all ages, and allow their members to work to the highest level of their training in an integrated fashion. Grouping care team members together within visual and auditory distance of each other is likely to enhance communication and teamwork, resulting in more efficient care for patients. This grouping is termed colocation. The authors describe how the use of colocation can lead to clearer, faster communication between care team members. This practice style has the potential to be expanded into various clinical settings in any given health system and to almost all clinical specialties and practices.